Bank directors' compensation among selected Asian emerging countries - Murugiah, Logasvathi; Ahmad, Nor Hayati (LAP LAMBERT Academic Publishing, 2012)
Directors with wide experience, leadership and managerial talents need to be attractively compensated especially in the highly competitive banking industry. The main objectives of this study are; to identity significant factors determining Board of Director Compensation (BODC) and to establish the linkage between BODC determinants and bank performance using Asian emerging countries. We employ multiple regression analysis and Structural Equation Modeling in this study. Finding shows that bank size is the most significant determinant. The impact of inflation, BOP and GDP are new findings since they have not been tested before on BODC studies across emerging Asian countries. The study shows experience and GDP have direct path and significant relationship with BODC and bank performance. This study is significant since it would probably be one of the earliest studies which utilize SEM to show the relationship between internal and external factors that influence BODC and the linkage between BODC to bank performance. The findings from SEM provide contribution to new knowledge in terms of the direct and indirect effects of the determinants on BODC and bank performance.